Moving Towards Europe Diverse Trajectories and Multidimensional Drivers of Migration across the Mediterranean and the Atlantic - Selin Okyay, Asli; Barana, Luca; Boland, Colleen Elizabeth (Global Politics and Security, 2023)
Population movements taking place in past decades, including those reaching the European Union, defy straightforward and simplistic conceptions of drivers, trajectories and forms of migration. Approaching migration journeys as non-linear processes, this book looks into the conditions and legal-policy frameworks at broad spaces of mobility interlinking several origin, transit, destination and host contexts in South/Central/Western Asia, Eastern/Central/Western Africa, Central and South America, and Europe to provide a more nuanced understanding of mixed migration. It also looks at specific migratory trends towards the European Union before and after the so-called 'migration crisis' (2009-2020), while paying particular attention to gender- and sexuality-specific dynamics and patterns.